Na2MnGe2Se6: a new Mn-based antiferromagnetic chalcogenide with large Mn⋯Mn separation. Issue 46 (8th November 2016) - Zhou, Molin; Yin, Wenlong; Liang, Fei; Mar, Arthur; Lin, Zheshuai; Yao, Jiyong; Wu, Yicheng
Abstract : Despite the large spatial separation of Mn⋯Mn ions, Na2 MnGe2 Se6 still exhibits an interesting antiferromagnetic transition. Abstract : A new one-dimensional (1D) Mn-based chalcogenide Na2 MnGe2 Se6 has been obtained by a solid-state reaction. It crystallizes in the tetragonal space group I 4/ mcm with unit cell parameters a = 7.7718(16) Å, b = 7.7718(16) Å, c = 19.077(7) Å and Z = 2. In the structure, MnSe4 and GeSe4 tetrahedra are linked alternately via edge-sharing with a ratio of 1 : 2 to form 1D infinite [MnGe2 Se6 ] 2− anionic chains, which are further separated by Na + cations. Such a spatial arrangement leads to large separations between magnetic ions, namely, 9.538(5) Å for the nearest intrachain Mn⋯Mn distance and 5.495(5) Å for the neighboring interchain Mn⋯Mn distance. Despite the large Mn⋯Mn separation, the temperature dependent susceptibility measurement and specific heat measurement still indicate an interesting antiferromagnetic interaction with the Néel temperature T N = 11 K for this compound. Such unusual magnetic properties have been seldom reported in other Mn chalcogenides. The magnetic interaction is investigated by the spin-polarized calculations. Besides, the UV-vis-NIR spectroscopy measurement indicates that Na2 MnGe2 Se6 has an indirect band gap of 1.93 eV.